In Spite of 110 Years of Lill 'S Law -110 Years Basic Mistakes in Transport Science - Hermann Knoflacher (Communications - Scientific letters of the University of Zilina, 1999)
Lills law, published 1889 includes implicitly the so-called “time constancy“ for mobility which was found in many empirical studies during the last decades, worldwide. It can be shown that Lills law can be derived from a more basic human behaviour law, discovered by Weber and Fechner in the 19th century. The knowledge of this law helps us to a better understanding of the mechanisms of modern transport systems and to find solutions which are more cause-related.